Prognostic value of PaO2/FiO2, SOFA and D-dimer in elderly patients with sepsis. Issue 6 (June 2022) - Li, Tao; Hu, Wan-Qin; Li, Xian; Zhang, Jia-Peng; Tan, Li-Zhi; Yu, Li-Xia; Gu, Hai-Rong; Shi, Ze-Ya
Objective: To investigate the prognostic value for predicting mortality of partial pressure of oxygen/fraction of inspired oxygen (PaO2 /FiO2 ), the Sequential Organ Failure Assessment (SOFA) score and D-dimer in elderly patients with sepsis. Methods: This retrospective cohort study enrolled elderly patients with sepsis admitted to the intensive care unit (ICU) between January 2019 and October 2020. Patients were divided into a survival group and a non-survival group. Biomarkers, SOFA, Acute Physiology and Chronic Health Evaluation II and Glasgow Coma Scale scores were recorded within 24 h after admission to the ICU. Results: A total of 135 elderly patients with sepsis were enrolled in the study: 89 were in the survival group and 46 were in the non-survival group at 28 days. Univariate and multivariate regression analyses demonstrated that PaO2 /FiO2, SOFA and D-dimer were independently associated with 28-day mortality. The predictive performance for mortality of the combination of PaO2 /FiO2, SOFA score and D-dimer (area under the receiver operating characteristic curve of 0.926) was higher than the values for the individual factors (0.761, 0.745 and 0.878, respectively). Conclusion: The combination of PaO2 /FiO2, SOFA score and D-dimer represents a promising tool and biomarker for predicting 28-day mortality of the elderly patients with sepsis.